Pendampingan Kunjungan Belajar Implementasi Dana Awal Otonomi Khusus Papua - Bleskadit, Novalia Herlina; Hosio, Y Flora; Bayani, Kornelia; Purnama, Chaterina; Yable, Kris; Imbiri, Liana (The Community Engagement Journal, 2024)
The study visit activity is a service activity which aims to provide understanding to students and supervisors from ASNs at the Papua Province BAPPEDA office as resource persons on the study visit. The methods or stages in implementing this service are the preparation stage, implementation stage and evaluation stage. As a result of this service activity in the form of a study visit, it can be concluded that the process of understanding the initial stages of the policy of the Special Autonomy Law or Law Number 21 of 2001 is the beginning of the implementation of the special autonomy program from a term of office of 5 (five) years during the period of Provincial Governor Papua, Father Jacobus or Jaap Salossa, whose leadership implemented the Special Autonomy Law. With several criteria, the results of the evaluation of the 2002-2006 Special Autonomy Fund Allocation that have been evaluated have several recommendations that will be implemented in the period after 2006 by the next Governor of Papua Province. Apart from that, the realization of this study visit activity by the community service team of students and supervisors at the Faculty of Economics & Business, Ottow Geissler University Papua has proven that understanding of Special Autonomy from BAPPEDA data is very reliable to increase knowledge about the rules and allocation of funds in Land of Papua. Keywords: Initial Implementation of Special Autonomy in 2002-2006, Study Visits, Allocation of Special Autonomy Funds